Collaboration in the rural schools of the Eden/Karoo District and the use of knowledge management tools - Webber, Zwelibanzi Samson (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2008.